2012
DOI: 10.1002/qj.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sequential or simultaneous assimilation of observations and localization methods on the performance of the ensemble Kalman filter

Abstract: The various implementations of the ensemble Kalman filter (EnKF) differ from each other in several ways. The effects of these differences are not yet well and completely explored and they include the use of sequential or simultaneous assimilation of observations and the application of localization to the observation error covariance matrix (R-localization) or the background error covariance matrix (B-localization). This study seeks to examine and better understand the effects of these differences, both individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 33 publications
(67 reference statements)
1
27
0
Order By: Relevance
“…2) EnKF assimilated observations sequentially whereas 3DEnsVar1way assimilated all observations simultaneously. A recent study by Holland and Wang (2013) suggested that the simultaneous/sequential assimilation in combination with different covariance localization methods could lead to performance differences in the ensemble-based data assimilation. 3) The ensemble smoother version of EnKF was adopted where effectively the fourdimensional ensemble covariance was utilized during the 6-h assimilation window.…”
Section: Gsi3dvarmentioning
confidence: 99%
See 1 more Smart Citation
“…2) EnKF assimilated observations sequentially whereas 3DEnsVar1way assimilated all observations simultaneously. A recent study by Holland and Wang (2013) suggested that the simultaneous/sequential assimilation in combination with different covariance localization methods could lead to performance differences in the ensemble-based data assimilation. 3) The ensemble smoother version of EnKF was adopted where effectively the fourdimensional ensemble covariance was utilized during the 6-h assimilation window.…”
Section: Gsi3dvarmentioning
confidence: 99%
“…The background ensemble covariance could also become more balanced due to the 6-h spinup during the forecast steps of the data assimilation cycling. On the other hand, the covariance localization applied to the ensemble covariance could degrade the balance (e.g., Lorenc 2003;Kepert 2009;Holland and Wang 2013). The impact of the TLNMC on the ensemble increment was therefore investigated.…”
Section: Impact Of Tlnmc Balance Constraintmentioning
confidence: 99%
“…Whitaker et al (2008) also compared the assimilation performance of the EnSRF with the LETKF when applied with a global atmospheric model and found only small differences. Similarly, Holland and Wang (2013) compared the LETKF with the EnSRF without particular observation ordering for the assimilation with a simplified atmospheric model. They found only small differences in the state estimates with slightly smaller errors in the LETKF estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Additional efforts include the successive covariance localization (Zhang et al 2009) and the multi-scale localization approach Kondo et al 2013). More information about comparing simultaneous and sequential assimilation can be found in (Holland et al 2013). …”
Section: Discussionmentioning
confidence: 99%